Impact of the COVID-19 pandemic on adults accessing specialist psychiatric care: A cross-sectional Canadian analysis - Mary E. Kittur; Brett D. M. Jones; Shayan Imran; Wei Wang; Sheng Chen; Muhammad Ishrat Husain (PLoS ONE, 2026)
Background The COVID-19 outbreak presented significant psychological challenges, placing individuals with pre-existing psychiatric conditions at disproportionate risk. Identifying the pandemic-related factors driving mental health outcomes in this population is essential to inform targeted interventions during future public health crises. Objectives To examine associations between COVID-19-related stressors and psychological symptom severity among Canadian adults with pre-existing mental health conditions during the first two years of the pandemic. Methods This cross-sectional study administered a web-based survey to outpatients accessing specialist psychiatric services in Toronto, Canada, between May 2020 and March 2022, aligning with the first five COVID-19 infection “waves” in the region. A series of linear regression models assessed associations between pandemic-related factors (COVID-19 fears, FCV-19S; consumed pandemic-related media; coping responses, Brief-COPE) and symptoms of anxiety (GAD-7) or depression (PHQ-9). Results 362 participants completed the self-report survey (70% female, mean age 33.8 ± 11.7). Anxiety (60.2%) and depression (59.1%) were the most frequently reported pre-existing psychiatric conditions. Depressive and anxious symptoms met thresholds for “moderate” severity during all five pandemic waves. Greater fear of COVID-19 was associated with increased symptoms of depression ( β = 0.12, 95% CI: 0.01, 0.22) and anxiety (β = 0.25, 95% CI: 0.16, 0.35). Avoidant and emotion-oriented coping predicted increased psychological symptoms ( p < .001), while problem-focused coping was associated with lower depression scores ( β = −0.15, 95% CI: −0.28, −0.02). Frequency of pandemic-related media consumption showed no significant association with any psychological symptoms ( p > .05). Conclusions Canadians with pre-existing mental health conditions experienced persistently elevated psychological symptoms throughout the first two years of the COVID-19 pandemic. COVID-related fear and maladaptive coping emerged as key drivers of symptom severity, while problem-focused coping showed a protective effect, suggesting modifiable treatment targets. Findings underscore the importance of interventions targeting fear attenuation and adaptive coping to protect psychiatric patients during a prolonged public health crisis. Future research should extend investigations globally to determine the broader mental health impact of pandemic stressors in patient populations. Ultimately, findings support the integration of sustained psychological support within emergency response protocols to mitigate the psychological burden of future pandemics and health crises.